SINERGITAS GURU PAI DAN GURU BK DALAM MENJAGA KEDISIPLINAN (Studi Kasus Kelas X SMK Negeri 3 Jombang) - Usman Wahyu Sudrajat; Nur 'Azah (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Education is a process to develop students' potential, where obedience is important in character building. In SMK Negeri 3 Jombang, violations often occur, such as lateness and absence. Islamic Religious Education (PAI) and Guidance and Counseling (BK) teachers play a role in fostering student obedience through religious values ​​and counseling. Collaboration between the two is essential for effective coaching. This study has three objectives: 1) To compile and analyze the collaboration between PAI teachers and BK teachers. 2) To analyze the level of obedience of class X students. 3) To analyze the elements that support and hinder the synergy of PAI and BK teachers in maintaining student obedience.This study uses a qualitative and descriptive approach, with data collection through interviews, observations, and documentation from the principal, teachers, and students. The findings show that the synergy between PAI and BK teachers is important in shaping obedience, despite the challenges faced by class X students.